Factors associated with negative co-parenting experiences in families of a child with autism spectrum disorder - Sim, Amelia; Cordier, Reinie; Vaz, Sharmila; Netto, Julie Ann; Falkmer, Torbjorn (2016)
Purpose: The purpose of this study was to identify key factors associated with negative co-parenting experiences in parents raising a child with autism spectrum disorder. Methods: Questionnaires were sent to families with one or more children with a diagnosis of autism spectrum disorder. Parents of 142 children with autism spectrum disorder indicated that the diagnosis had a very negative impact on their co-parent relationship. A multivariate logistic regression model was run to analyze the association of these experiences with various demographic, family and community factors. Results: Three factors were associated with negative co-parenting relationships: (1) family stress due to the child’s diagnosis, (2) effects of the diagnosis on parents’ relationship with their other children and (3) distance travelled to the nearest medical facility. Conclusions: Findings highlight the need to further explore family dynamics, particularly the relationships between the co-parenting alliance, other family members and the extra-familial environment.